Pengaruh Pelepasan Panas Terhadap Prestasi Kerja Mesin Bensin - Tri Susilo Wirawan (Jurnal Teknik Mesin Indonesia, 2024)
Gasoline engines are crucial in various human activities, especially in the transportation sector. The aim of this study is to determine the performance of commonly used fuels, namely Pertamax and Pertalite. The results of the research show that Pertamax fuel performs better than Pertalite, as evidenced by the heat and working pressure produced.